Is a motivational interviewing based lifestyle intervention for obese pregnant women across Europe implemented as planned? Process evaluation of the DALI study - Judith G. M. Jelsma; David Simmons; Nina Gobat; Stephen Rollnick; Kinga Blumska; Goele Jans; Sander Galjaard; Gernot Desoye; Rosa Corcoy; Fabiola Juarez; Alexandra Kautzky-Willer; Jürgen Harreiter; et al. (BMC, 2017)
Abstract Background Process evaluation is an essential part of designing and assessing complex interventions. The vitamin D and lifestyle intervention study (DALI) study is testing different strategies to prevent development of gestational diabetes mellitus among European obese pregnant women with a body mass index ≥29 kg/m2. The intervention includes guidance on physical activity and/or healthy eating by a lifestyle coach trained in motivational interviewing (MI). The aim of this study was to assess the process elements: reach, dose delivered, fidelity and satisfaction and to investigate whether these process elements were associated with changes in gestational weight gain (GWG). Methods Data on reach, dose delivered, fidelity, and satisfaction among 144 participants were collected. Weekly recruitment reports, notes from meetings, coach logs and evaluation questionnaires (n = 110) were consulted. Fidelity of eight (out of twelve) lifestyle coach practitioners was assessed by analysing audio recorded counselling sessions using the MI treatment integrity scale. Furthermore, associations between process elements and GWG were assessed with linear regression analyses. Results A total of 20% of the possible study population (reach) was included in this analysis. On average 4.0 (of the intended 5) face-to-face sessions were delivered. Mean MI fidelity almost reached 'expert opinion' threshold for the global scores, but was below 'beginning proficiency' for the behavioural counts. High variability in quality of MI between practitioners was identified. Participants were highly satisfied with the intervention, the lifestyle coach and the intervention materials. No significant associations were found between process elements and GWG. Conclusion Overall, the intervention was well delivered and received by the study population, but did not comply with all the principles of MI. Ensuring audio recording of lifestyle sessions throughout the study would facilitate provision of individualized feedback to improve MI skills. A larger sample size is needed to confirm the lack of association between process elements and GWG. Trial registration ISRCTN registry: ISRCTN70595832 ; Registered 12 December 2011.